Linguistic distances between native languages and Chinese influence acquisition of Chinese character, vocabulary, and grammar - Chai, Xingsan; Bao, Jie (Frontiers in Psychology, 2023)
How linguistic distance affects second language acquisition is a major concern in cross-language transfer research. However, no study has explored how systematic differences between Chinese and learners’ native language (L1) influences Chinese character, vocabulary, and grammar acquisition, or how these influence change as Chinese proficiency improves. To address this, we employed the World Atlas of Language Structures (WALS) index method to multidimensionally quantify the linguistic distance between Chinese and L1, and examined the effect of systematic linguistic distance on acquisition of Chinese character (Quasi-Experiment 1), vocabulary (Quasi-Experiment 2), and grammatical knowledge (Quasi-Experiment 3) in Chinese as a second language (CSL) learners with elementary, intermediate, and advanced Chinese proficiency levels. We examined a random sample of 58,240 CSL learners’ test scores from 24 different L1 backgrounds, and analyzed 2,250 CSL learners’ Chinese character, vocabulary, and grammar scores in each of the three quasi-experiments. We found that closer linguistic distance facilitated more favorable Chinese character and vocabulary acquisition at elementary, intermediate, and advanced Chinese proficiency levels, and that the influence of linguistic distance on CSL learners’ vocabulary acquisition tended to decrease as Chinese proficiency increased. Finally, linguistic difference did not significantly affect CSL learners’ grammar acquisition at elementary proficiency, but as Chinese proficiency improved, an L1 interference effect occurred among CSL learners with a short linguistic distance from Chinese, which hindered grammar acquisition. These results suggest that linguistic distance has differential proficiency-dependent effects on Chinese character, vocabulary, and grammar acquisition.